Breast dermatofibrosarcoma protuberans with latissimus dorsi reconstruction. A case report - Guevara Pacheco, Jhon (2023)
Dermatofibrosarcoma protuberans is a fibro histiocytic cutaneous tumor extremely rare that accounts for less than 1% of all breast cancers, and it is characterized by slow growing but locally invasiveness with high recurrence rates. Confirmation of the diagnosis is with histopathology with immunohistochemistry. Treatment of choice is surgical resection with latissimus dorsalis reconstruction. We present the case of a 23-year-old woman with dermatofibrosarcoma protuberans of the right breast in whom a tumorectomy followed by latissimus dorsalis reconstruction was performed. The patient had a favorable clinical evolution remaining free of disease.